ANALISA RISIKO PROYEK PEMBANGUNAN FLY OVER JALAN JUANDA â ABDUL WAHAB SYAHRANI SAMARINDA - Kurniawan Rosady, Benny Mochtar, Purwanto dan (KURVA S, 2016)
Risk is one of the things that can not be separated in their daily lives . In the implementation of construction projects are also not immune from risk . Required a risk management approach to identify and control the risks that might occur in the future . One of the most important stage of risk management is risk analysis that aims to identify significant risks to the project. In this study will be conducted on a risk analysis Development Project Fly- Over juanda road - Abdul Wahab Syahrani samarinda . Stages of this research can be divided into three parts, namely risk identification , risk analysis and risk response . Identification is looking for a stage variables relevant risk on the project . Risk analysis is the process of looking for some significant risks in terms of time and cost The method used in risk analysis is Severity Index and Probability - Impact Matrix .The last stage is to determine the response of the risks to a significant risk of cost and time . Risk response obtained by conducting structured interviews with the respondents that some contractor personnel who handle development projects juanda the Fly - Over - Abdul Wahab Syahrani samarinda . Based on the results of the risk analysis obtained 6 kinds of variables are significant risks with respect to time , which hampered the work of rainy weather conditions , the difficulty of bringing the equipment , material delivery delays , delays in implementation while erection , while drilling constraints , bottlenecks in traffic . While significant risks to the variable costs are 5 kinds of risks , namely workers affected by material , workers hit heavy equipment , damage to the equipment , tools and material theft , damage to the environment due to the project